ThoughtIbn Sina's Islamic Education: Relevance to Contemporary Education - Syahrani, Amellia Putri; Jumiati, Dinda; Dewi, Eva (STIT Ahlussunnah Bukittinggi, 2025)
Education is a conscious and planned effort to create a learning environment and learning process so that students can develop their potential to have spiritual strength. One of the famous Muslim scientists known for his knowledge is Ibn Sina, who emphasized the integration of rationality and morality, as well as the holistic development of individuals. This study aims to analyze Ibn Sina's concept of education in terms of objectives, curriculum, methods, and the role of educators, and to assess how this concept can be applied in the modern Islamic education system. This article examines the Islamic educational thinking of Ibn Sina, one of the greatest polymaths in the history of Islamic civilization. Through a descriptive-analytical approach, this study outlines the basic concepts, objectives, curriculum, learning methods, and concepts of teachers and students from Ibn Sina's perspective. The results of the study show that Ibn Sina's educational thinking is holistic and integral, combining spiritual and rational aspects into a harmonious whole. Principles such as ta'dib (character building), tadrij (gradualism), individualization, and integration of knowledge demonstrate the sophistication of his thinking, which is relevant to the challenges of contemporary Islamic education, particularly in addressing the dichotomy of knowledge, moral crisis, and the need for individualized learning. Implicitly, Ibn Sina's thinking encourages a holistic contemporary Islamic education curriculum that combines intellectual, physical, social, and spiritual aspects and emphasizes that character building (morals, responsibility, honesty) must be an integral part of the learning process